Temporal logic learning-based anomaly detection in metroplex terminal airspace operations. (May 2021) - Deshmukh, Raj; Sun, Dawei; Kim, Kwangyeon; Hwang, Inseok
Highlights: Detecting outliers (anomalies) is critical in safety-related applications like ATM. Metroplex airspace is most congested and highly-coordinated of all components of ATM. ATM data capturing technologies enables data-driven approach to improving safety and throughput. The anomaly detection algo must be interpretable, and it must evolve with and adapt to airspace. This is best achieved through ingesting both operational, and real-time surveillance data. Abstract: The airspace system is a complex dynamical system with complicated controlled interactions between its constituent subsystems – terminal airspace, en-route airspace, and ground. Of these, air traffic management in the multi-airport (metroplex) terminal airspace is one of the most complicated subsystems to manage, especially due to the interactions between proximal airports. Analyzing anomalous behaviors in the metroplex is emerging as a key problem in understanding air traffic management complexity and safety. Although physics-based approaches have been studied in-depth for this application, newfound interest has been observed to use recorded time-series air traffic surveillance and airport operations datasets for this purpose. In this paper, we propose a machine learning-based anomaly detection algorithm that generates mathematical models to detect anomalies in metroplex operations. Several machine learning algorithms have been developed to detect anomalies using only air traffic surveillance data, but there is a significant scope of improvement by including airport operational characteristics as well, since integrating such closely-controlled metroplex operational datasets allows the developed models to effectively detect anomalies. The key contribution of this paper is in allowing anomaly detection models to recursively update so as to adapt to changes in metroplex operations. The proposed algorithm is demonstrated with real air traffic surveillance and airport operations datasets at LaGuardia, John F. Kennedy, and Newark airports, thereby detecting anomalies for operations in the New York metroplex.